2018
DOI: 10.1111/sms.13317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin application on the skin during resting exposure to temperate and warm conditions

Abstract: We investigated thermoregulatory and cardiovascular responses at rest in a temperate (20°C) and in a warm (30°C) environment (40% RH) without and with the application of capsaicin on the skin. We hypothesized that regardless of environmental temperature, capsaicin application would stimulate heat loss and concomitantly deactivate heat conservation mechanisms, thus resulting in rectal temperature (Tre) and mean blood pressure decline due to excitation of heat‐sensitive TRPV1. Ten male subjects were exposed, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…As a consequence, the cycling time needed for subjects' rectal temperature to reach 38.2°C was increased by 5 min approximately in capsaicin compared to the noncapsaicin condition. The present findings are in accordance with our previous work in resting humans (Botonis et al, 2019), indicating that capsaicin application on the skin (5% of the skin surface area) induces significant rectal temperature decline as a result of TRPV1 activation. Extending this knowledge, the present study showed that during cycling, the estimated vasoconstrictive tone was lower and the sweating rate was higher, with its initiation occurring at lower rectal temperature rise, after capsaicin application, thus resulting in a slower rectal temperature increase.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…As a consequence, the cycling time needed for subjects' rectal temperature to reach 38.2°C was increased by 5 min approximately in capsaicin compared to the noncapsaicin condition. The present findings are in accordance with our previous work in resting humans (Botonis et al, 2019), indicating that capsaicin application on the skin (5% of the skin surface area) induces significant rectal temperature decline as a result of TRPV1 activation. Extending this knowledge, the present study showed that during cycling, the estimated vasoconstrictive tone was lower and the sweating rate was higher, with its initiation occurring at lower rectal temperature rise, after capsaicin application, thus resulting in a slower rectal temperature increase.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study in humans (Botonis et al, 2019), confirming previous observations in animals (Donnerer & Lembeck, 1983;Jansco-Cabor, Szolcsanyi, & Jancso, 1970), demonstrated a significant rectal temperature decline during resting conditionas a result of capsaicin application on subjects' skin. Along these lines, studies conducted in vivo have shown that TRPV1 channels contribute to thermal hyperaemia (Wong & Fieger, 2010) accompanied by cutaneous active vasodilation (Wong & Fieger, 2012).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations